Synthesis and biological evaluation of α-sulfonamido-N-adamantanecarboxamide derivatives as 11β-HSD1 inhibitors. Issue 7 (8th July 2015) - Kim, Young Hoon; Kang, Seung Kyu; Lee, Gwi Bin; Lee, Kyu Myung; Kumar, Jaladi Ashok; Kim, Ki Young; Rhee, Sang Dal; Joo, Jeongmin; Bae, Myung Ae; Lee, Won Koo; Ahn, Jin Hee
<x xml:space="preserve">Abstract</x> A series of α-sulfonamido-N-adamantanecarboxamide derivatives was synthesized and shown to have good in vitro and ex vivo efficacy.